Traversing the Ridge: Experiences of Nurses on their Licensure Examination (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2021)
The sole purpose of a licensing examination is to identify persons who possess the minimum knowledge and experience necessary to perform tasks on the job safely and competently--not to select the “top” candidates or ensure the success of licensed persons. This study explored the lived experiences of nurses on their licensure examination, guided by the question “What are your lived experiences as a nurse on your licensure examination the study utilized qualitative research, specifically, Husserlian phenomenology. The sixteen participants were chosen through criterion sampling with the approval of the Ethics Review Board before the gathering of data. The data were collected from March 2021-April 2021. Giorgi's method of interpretation was utilized in analyzing data and was simultaneously done with data gathering. The themes that emerged from this study were the terrain, the narrow ridge, and the peak. The participants stated that takingtheNLEcanbecomparedintraversingaridge.Theyhavementionedthatthereisno shortcut to experience, and the more time they have spent preparing for the ridge traverse beforehand, the greater their chance of success. Likewise, prior knowledge of key sections plays in their favor and helps them reach their peak. Therefore, it is recommended that nurse educators and curriculum planners make a positive contribution toward minimizing the stress of student nurses who will take the NLE. Furthermore, it is important that parents spend quality time with their children because this ascertains their physical and emotional availability. In addition, this, in turn, will help them succeed in taking the NLE.
Keywords: Nurses Licensure Examination, anxiety, hope, success